Alzheimer's Disease Memoirs - Nayar, Pramod K. author. aut Link
XIII, 153 p. 1 illus.
Keywords: This book examines writings by people living with Alzheimer's Disease and their caregivers. Its focus areas include the construction of the self in the face of diminishing linguistic and cognitive abilities, the stigmatization of ageing, the various narrative strategies that these texts (often collaborative) employ, the health activism and advocacy generated via a 'biosociality,' and the ethics of care. It examines the 'disease writing' genre about a condition that ravages the ability to use language. It serves as a "literary" examination of the work done in this area through a critical reading of the memoirs of those with AD and caregivers and a healthy dose of literary theory. The book is a valuable resource for those interested in literary and critical theory and researchers in the field of ageing/dementia studies.